(untitled) (Environment & Health, 2020)
Pesticides are among the chemicals most studied in terms of adverse effects on the thyroid gland. However, agriculture in most countries, especially developing ones, is heavily reliant on pesticide application, which prevents or reduces losses from pests and thus increases yields and product quality, even in terms of external attractiveness, which is often important for consumers. Objective:The aim of the study is a hygienic substantiation of the selection criteria for monitoring and assessment of the human health risk of pesticides that may affect the thyroid gland. Materials and methods: We used methods of laboratory and field hygiene experiments, physico-chemical (chromatographic), organoleptic, physical methods, methods of mathematical modeling and statistical analysis. Results and discussion: When deciding on the need for monitoring in Ukraine for a pesticide that affects the thyroid gland, each of the proposed indicators have to be evaluated in points and their total value have to be estimated. If formulations based on the test compound are used on different crops or in different soil and climatic conditions, the maximum values of the half-life periods should be taken for the assessment.After adding all points received, the need for monitoring is evaluated as follows: for a total of 11-16 points – monitoring is not required; 17-27 points – monitoring is desirable; 28-38 –monitoring is obligatory; 39-44 – pesticide use should be prohibited. Conclusion: Thus, we have improved the monitoring system of pesticide that may affect the functioning of the thyroid gland, namely: it offered a point evaluation of the selection criteria for monitoring studies, proposed additional (the Groundwater and Surface Water Pollution Index (LEACH); indices of the hazard of entry into the human body (integral index of contaminated water consumption hazard (IICWCH) and the integral index of contaminated food consumption hazard (IICFCH)) and specific criteria (effect on thyroid gland as target organ, severity of pesticide induced tyrosinemia (plasma tyrosine level, nmol/ml).